2000
DOI: 10.4049/jimmunol.165.3.1314
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Natural Killing of MHC Class I-Deficient Targets by NK Cells Expressing a Catalytically Inactive Form of SHP-1

Abstract: NK cell function is negatively regulated by MHC class I-specific inhibitory receptors. Transduction of the inhibitory signal involves protein tyrosine phosphatases such as SHP-1 (SH2-containing protein tyrosine phosphatase-1). To investigate the role of SHP-1 for NK cell development and function, we generated mice expressing a catalytically inactive, dominant-negative mutant of SHP-1 (dnSHP-1). In this paper we show that expression of dnSHP-1 does not affect the generation of NK cells even though MHC receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 48 publications
2
42
0
2
Order By: Relevance
“…These results indicate that phosphorylation of the tyrosine residue in the ITIM is necessary for recruitment of SHP-1 and SHP-2 to Ly49Q. Thus, Ly49Q expressed on COS7 cells shows biochemical characteristics similar to other known Ly49 family members (12,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 54%
“…These results indicate that phosphorylation of the tyrosine residue in the ITIM is necessary for recruitment of SHP-1 and SHP-2 to Ly49Q. Thus, Ly49Q expressed on COS7 cells shows biochemical characteristics similar to other known Ly49 family members (12,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 54%
“…Most of the mouse NK cells express MHC class I-inhibitory receptors such as Ly49 receptors, which contain tyrosine residues capable of binding to the SH2 domains of a tyrosine phosphatase, SHP-1 upon phosphorylation and counteract the kinase activity by recruiting SHP-1. 27,28,30 There are several lines of evidence indicating that MHC class I-deficient tumor cells are susceptible to NK cells. 31,32 Our results also showed that MHC class I-negative B16.44 melanoma cells are susceptible to the poly I:C-activated NK cells.…”
Section: Effects Of In Vivo Depletion Of Nk Cells or Cd8 ϩ T Cells Onmentioning
confidence: 99%
“…[25][26][27][28] On the other hand, MHC class I-deficient melanoma is not destroyed by cytotoxic CD8 þ T cells but is susceptible to NK cells, most of which express MHC class I-specific inhibitory receptors. [29][30][31][32] In the present study, we examined the effects of oral administration of AC-1 on protection against 2 murine B16 melanoma lines, MHC class I-negative B16L and MHC class I gene-transfected B16K b cells. Tumor growth was severely retarded in AC-1-treated mice after subcutaneous inoculation with B16L or B16K b cells.…”
mentioning
confidence: 99%